2007
DOI: 10.1136/sti.2007.027441
|View full text |Cite
|
Sign up to set email alerts
|

Interventions among male clients of female sex workers in Benin, West Africa: an essential component of targeted HIV preventive interventions

Abstract: These results demonstrate that it is possible to implement preventive and clinical services for clients of FSWs, and suggest that such interventions, integrated with those targeted towards FSWs, can have a significant effect on sexual behaviour and STI prevalence (particularly gonorrhoea) among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 17 publications
1
57
0
1
Order By: Relevance
“…Further, most (70%) boyfriends of FSW in a study in Guinea and Benin reported having been clients of one or more sex workers other than their girlfriends [1]. HIV prevalence among boyfriends of FSW has also been shown to be higher than that among FSW clients: twice as high in a study in Benin (16.1% among boyfriends versus 8.3% among clients) [103], and even higher in Ghana (32.1% among boyfriends versus 4.9% among clients of mobile sex workers and 15.8% among clients of home-based sex workers) [104]. These patterns suggest that sex work in sub-Saharan Africa cannot be viewed in isolation from HIV-risk behaviors in the general population, such as multiple concurrent partnerships.…”
Section: Unsafe Sexmentioning
confidence: 88%
“…Further, most (70%) boyfriends of FSW in a study in Guinea and Benin reported having been clients of one or more sex workers other than their girlfriends [1]. HIV prevalence among boyfriends of FSW has also been shown to be higher than that among FSW clients: twice as high in a study in Benin (16.1% among boyfriends versus 8.3% among clients) [103], and even higher in Ghana (32.1% among boyfriends versus 4.9% among clients of mobile sex workers and 15.8% among clients of home-based sex workers) [104]. These patterns suggest that sex work in sub-Saharan Africa cannot be viewed in isolation from HIV-risk behaviors in the general population, such as multiple concurrent partnerships.…”
Section: Unsafe Sexmentioning
confidence: 88%
“…Our results, combined with the condom use rates reported in our literature review (KHPT and University of Manitoba 2008) thus reaffirm the relevance of continuing with condom-use promotion in South India. However, for this to reach its full potential, activities targeting the structural and cultural factors underlying the gender inequalities in relationships in South India should be developed and should take into account the complexities of the factors determining condom use (McMillan and Worth 2011), as well as the need to involve both female sex workers and their clients in interventions (Blankenship et al 2008;Lipovsek et al 2010;Lowndes et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The Indian national response had variable, but in general, low coverage of core groups, namely female sex workers (FSW), high-risk men who have sex with men (MSM)/transgender individuals and injecting drug users (IDU) [21,29,30]. Globally, there was evidence that intervening with core and bridge groups in early and concentrated epidemics translated into HIV reduction among general populations [27,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. At the time there were few examples of large-scale HIV prevention interventions [1,33,37,38,[46][47][48].…”
Section: Avahan the India Aids Initiativementioning
confidence: 99%